Universities Through the Looking Glass : Benchmarking University Governance to Enable Higher Education Modernization in MENA - World Bank (Washington, DC, 2013)
This benchmarking exercise provided some important lessons on the tool itself and its capacity to: 1) identify strengths and weaknesses at individual institutions; 2) identify trends at the national level; 3) identify trends and practices by type of institution; and 4) generate interest to initiate reforms at the institutional, national, and regional levels. It is clear from this first round of data collection (and the subsequent increased demand and interest from institutions to participate), that universities are seeking to find meaningful ways to compare themselves with other institutions around the world, but more importantly, that they are genuinely interested in finding ways of improving their performance. Countries in the Middle East and North Africa (MENA) region are going through an important political transformation, and this is likely to impact their economic and social development for the next few years. The January 2011 revolution in Tunisia and Egypt's uprising transformed the political and social environments in both countries. In all MENA countries, recovery will depend on the capacity to develop new markets and to employ fiscal prudence. Universities play a key role in all societies because they are directly involved in generating new knowledge and because they teach and form young people to become leaders, entrepreneurs, scientists, and professionals in all fields of knowledge. In today's world, knowledge generation has replaced capital assets as the key ingredient for economic growth. Universities need to innovate to provide the kind of education that will enable their graduates to be competitive and to contribute to the economic and social growth of their countries.